2011
DOI: 10.1002/dac.1338
|View full text |Cite
|
Sign up to set email alerts
|

Network Mobility in satellite networks: architecture and the protocol

Abstract: SUMMARY Mobility management is required to ensure the session continuity for multiple Internet Protocol‐enabled devices onboard a satellite that hands off between ground stations. Network Mobility (NEMO) can efficiently manage the mobility of multiple Internet Protocol‐enabled devices that are connected as a mobile network. However, existing mobility management solutions for satellite networks are unable to route through intermediate satellites links when a direct connection with a ground station is lost. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Recent improvements for vertical handover process suggest selection of appropriate access technology between WiFi and WiMAX based on analytical hierarchical process [17], an architecture based on MIH signalling for handover process between WiFi and LTE-Advanced [18], an architecture of network mobility (NEMO) in satellite link based on sensing information [19], and a game-theoretic model for selecting suitable access network by capturing inter-linkages of various networks [20]. In a highway with vehicles moving at high speeds in different directions, the authors [21] suggest pre-handover procedure to maintain internet connectivity, using vehicular ad hoc networks (VANETs).…”
Section: Related Workmentioning
confidence: 99%
“…Recent improvements for vertical handover process suggest selection of appropriate access technology between WiFi and WiMAX based on analytical hierarchical process [17], an architecture based on MIH signalling for handover process between WiFi and LTE-Advanced [18], an architecture of network mobility (NEMO) in satellite link based on sensing information [19], and a game-theoretic model for selecting suitable access network by capturing inter-linkages of various networks [20]. In a highway with vehicles moving at high speeds in different directions, the authors [21] suggest pre-handover procedure to maintain internet connectivity, using vehicular ad hoc networks (VANETs).…”
Section: Related Workmentioning
confidence: 99%
“…In order to ensure the security of satellite communication in open network, in 1996, the first security satellite communication scheme was proposed by Cruickshank, after which numerous LEO satellite communication schemes were proposed. However, many security problems were found in these schemes.…”
Section: Introductionmentioning
confidence: 99%
“…proposed an authentication and key agreement protocol to improve the scheme of Chen et al . They demonstrated that the protocol was effective in countering the disruptive effects of jamming . However, Chang et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, Lasc et al pointed out that the scheme is vulnerable to a denial of service attack. In 2011, Lasc et al proposed an authentication and key agreement protocol to improve the scheme of Chen et al They demonstrated that the protocol was effective in countering the disruptive effects of jamming [7]. However, Chang et al pointed out that the scheme of Lasc et al cannot resist the impersonation attack when the smart card is lost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation